Adaptabilidade e estabilidade da produtividade de 16 genótipos de soja resistente a herbicida em duas regiões sojícolas - Oliveira, Leonardo Gonçalves (2009)
This work aimed to evaluate the adaptability and stability of 16 soybean genotypes, being 6 strains from Monsoy Ltda s soybean breeding program and 10 check. The experiments were conducted in the harvests 2006/2007 and 2007/2008 in the soy microregions 301 and 401. The experimental design was the randomized block design with three repetitions. Individual and joint analyses were accomplished considering the productivity of the genotypes in different places and the averages were compared by the Scott and Knott test (1974). The adaptability and stability of the genotypes were evaluated through the methods of Eberhart and Russel, Annicchiarico, Linn and Binn and Centroide. The methods of Annicchiarico, Linn and Binns, modified by Carneiro and Centroide, have shown consistency between them and have allowed the identification, among the evaluated genotypes, the ones with bigger stability and adaptability. The check M7908RR, M8199RR and BRS VALIOSA RR are of general stability and adaptability. The strains 4 and 5 and the check M7908RR, M7578RR and M7211RR, have been classified with high adaptability and stability in favorable environments and the check M8199RR to unfavorable environments. To the microregion analysis separately, the strains 4 and 5 and check BRS VALIOSA RR showed a bigger average of productivity in two years toward the microregion 301, and in the microregion 401 the check M7908RR, M7578RR and M7211RR, showed the better averages in two years. Comparing the environments amidst two microregions, it was noticed that the environments are quite different and this shows that the separation of these two microregions is worth enough when it is thought about evaluation of genotypes toward the adaptability and stability of soybean genotypes.